(untitled) - Raad, Haider K. (London, 2016)
This book, organized into eleven chapters, introduces the latest research findings and trends related to the design, fabrication processes and techniques used in the realization of wearable and flexible electronics
Keywords: Electronic engineering,Kỹ thuật điện tử,Điện tử công suất